2006
DOI: 10.1093/rheumatology/kel348
|View full text |Cite
|
Sign up to set email alerts
|

Role of TNFRp55 in Yersinia enterocolitica O:3-induced arthritis: triggering bacterial antigens and articular immune response

Abstract: TNFRp55-mediated immune mechanisms prevent ReA development after oral infection with Y. enterocolitica O:3. Yersinia OMPs are the relevant antigens triggering ReA. NO induction through TNFRp55 signalling could have a local antibacterial function to prevent ReA. This study could contribute to ReA-specific therapeutic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 21 publications
3
16
0
2
Order By: Relevance
“…However, TNF is also a critical cytokine in the protective host response against bacterial infection, including Y. enterocolitica (5,24), raising the question as to whether this cytokine plays a pathogenic or protective role in bacterial-induced ReA, a pathological entity that combines components of infection and autoimmunity. We recently demonstrated that TNFR p55 signaling confers protection against ReA induced by Y. enterocolitica O:3 (8). In addition, unfavorable evolution has been reported in patients with spondyloarthropathies under treatment with TNF blockers (37).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, TNF is also a critical cytokine in the protective host response against bacterial infection, including Y. enterocolitica (5,24), raising the question as to whether this cytokine plays a pathogenic or protective role in bacterial-induced ReA, a pathological entity that combines components of infection and autoimmunity. We recently demonstrated that TNFR p55 signaling confers protection against ReA induced by Y. enterocolitica O:3 (8). In addition, unfavorable evolution has been reported in patients with spondyloarthropathies under treatment with TNF blockers (37).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria were cultured as described earlier (8). Mice were starved for 8 h and then were infected orogastrically, with 1-5 3 10 8 yersiniae in 200 ml saline, using a gastric tube.…”
Section: Bacterial Culture and Infectionmentioning
confidence: 99%
See 3 more Smart Citations